Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
An outstanding philologist, Slavist, a historian of Polishliterature and culture Aleksander Brückner, in The EtymologicalDictionary of the Polish Language (1926-27) wrote thatconscience means „to think this way or that”. This definition itselfleads to a serious reverie, since we actually do not know whatconscience is, though we have a hint – in conscience manponders, belabours, judges.